2018
DOI: 10.1111/1744-9987.12758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Uremic Serum Residue on OATP1B1‐ and OATP1B3‐Mediated Pravastatin Uptake in OATP‐Expressing HEK293 Cells and Human Hepatocytes

Abstract: Patients with end‐stage renal disease have increased plasma concentrations of statins, which is a risk factor for rhabdomyolysis, as well as elevated levels of uremic toxins (UTs). We investigated the effects of uremic serum residue and UTs on organic anion‐transporting peptide (OATP1B1)‐ and OATP1B3‐mediated pravastatin uptake. We evaluated the effects of normal serum residue with four UTs (hippuric acid, 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furan propionate, indole‐3‐acetic acid, and 3‐indoxyl sulfate) and uremic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The transfection rate was determined to be greater than 80% and met the requirement of our design. HEK293T cells are currently one of the commonly used in vitro models for studying the relationship between drug transporters and substrates 25,26 . OATP1B1 transfected HEK-293T cells can express OATP1B1 and bind to transport ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfection rate was determined to be greater than 80% and met the requirement of our design. HEK293T cells are currently one of the commonly used in vitro models for studying the relationship between drug transporters and substrates 25,26 . OATP1B1 transfected HEK-293T cells can express OATP1B1 and bind to transport ions.…”
Section: Discussionmentioning
confidence: 99%
“…Because hepatocyte only accounts for 10% of rosuvastatin metabolism 29 and scutellarin has such a significant pharmacokinetic effect on rosuvastatin uptake, suggesting that this effect is more likely to occur on cell surface transporters. HEK293 cells do not express OATP1B1, and it is a model cell that is commonly used to investigate OATP1B1 transport 26 . In this study, we showed that OATP1B1 can mediate the inhibition of scutellarin on rosuvastatin uptake transfected HEK293T cells with high expression of OATP1B1.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown uremic toxins concentration, indoxyl sulfate (total: 163.8 ± 6.2 µM, unbound: 26.3 ± 2.4 µM) and hippuric acid (total: 208.7 ± 2.6 µM, unbound 106.1 ± 1.5 µM) (Values represent the mean ± S.E.) 16 . These K i and IC 50 are higher than concentration of uremic toxins in our uremic serum, in other words, BCRP seems not to be inhibited by sole uremic toxin, but uremic toxins and other components in uremic serum may co-inhibit that.…”
Section: Discussionmentioning
confidence: 93%
“…The organic anion transporting polypeptides (OATPs) are a different category of organic anion transporters involved in the uptake of uremic toxins in the endothelium. OATPs belong to the SLCO superfamily and they have been detected in various tissues, such as lung, liver, kidney, and brain [ 102 , 103 ]. Grube et al [ 104 ] showed that these transporters are expressed in the cardiac endothelium.…”
Section: Transporters and Receptors Of Uremic Toxins In The Endothmentioning
confidence: 99%